A study on the role of credit management unit of Telekom Malaysia Bhd (Kuching) / Faridah Ismail - Ismail, Faridah (1996)
One of the most important elements in the financial environment of a business is the accounts receivable function. This was because most of the business enterprise selling their products or services using credit terms. It is quite difficult for the seller to sells their products or services to the customer in cash terms. Therefore, the business enterprise needs to manage their accounts receivable effectively in order to generate more revenue to sustain their daily business operations.